Oral noribogaine shows high brain uptake and anti-withdrawal effects not associated with place preference in rodents. (July 2016) - Mash, Deborah C; Ameer, Barbara; Prou, Delphine; Howes, John F; Maillet, Emeline L
This study investigated the effects of noribogaine, the principal metabolite of the drug ibogaine, on substance-related disorders. In the first experiment, mice chronically treated with morphine were subjected to naloxone-precipitated withdrawal two hours after oral administration of noribogaine. Oral noribogaine dose dependently decreased the global opiate withdrawal score by up to 88% of vehicle control with an ED50 of 13 mg/kg. In the second experiment, blood and brain levels of noribogaine showed a high brain penetration and a brain/blood ratio of 7±1 across all doses tested. In a third experiment, rats given oral noribogaine up to 100 mg/kg were tested for abuse liability using a standard biased conditioned place paradigm. Noribogaine-treated rats did not display place preference, suggesting that noribogaine is not perceived as a hedonic stimulus in rodents. Retrospective review of published studies assessing the efficacy of ibogaine on morphine withdrawal shows that the most likely cause of the discrepancies in the literature is the different routes of administration and time of testing following ibogaine administration. These results suggest that the metabolite noribogaine rather than the parent compound mediates the effects of ibogaine on blocking naloxone-precipitated withdrawal. Noribogaine may hold promise as a non-addicting alternative to standard opiate replacement therapies to transition patients to opiate abstinence.